Studying DNA replication fork stability in Xenopus egg extract - Hashimoto, Yoshitami; Costanzo, Vincenzo (Methods in molecular biology (Clifton, N.J.), 2011)
A crucial process to ensure cell survival and genome stability is the correct replication of the genome. DNA replication relies on complex machinery whose mechanisms are being elucidated using different model systems. A major aspect of this process, which is an intense subject of investigation, is what happens when replication forks encounter obstacles impairing their progression such as modified bases, pausing sites, and single strand breaks. The detailed biochemical analysis of DNA replication in the presence of DNA damage has been impeded by the lack of a cell-free system recapitulating DNA replication. Here we describe assays based on the vertebrate Xenopus laevis egg extract to study the biochemical aspects of replication fork stability.